2018
DOI: 10.1016/j.sdentj.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards HIV/AIDS among dental students of Jazan University, Kingdom Saudi Arabia

Abstract: HIV/AIDS related knowledge and attitudes in dental students of Jazan University are comparable to other studies from Saudi but are poor when compared to other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 25 publications
9
34
3
1
Order By: Relevance
“…According to multivariable analyses, after the adjustment of potential confounding variables, the completion of relevant training programs was significantly associated with both more confidence in knowledge mastery and a higher total knowledge score. This is consistent with previous studies, which suggested additional training and education improved dental practitioners' knowledge of infection control (26,27). This finding highlights the importance for dental hospitals, clinics, and relevant professional societies to organize adequate training activities for HCWs before the resumption of dental services.…”
Section: Discussionsupporting
confidence: 91%
“…According to multivariable analyses, after the adjustment of potential confounding variables, the completion of relevant training programs was significantly associated with both more confidence in knowledge mastery and a higher total knowledge score. This is consistent with previous studies, which suggested additional training and education improved dental practitioners' knowledge of infection control (26,27). This finding highlights the importance for dental hospitals, clinics, and relevant professional societies to organize adequate training activities for HCWs before the resumption of dental services.…”
Section: Discussionsupporting
confidence: 91%
“…The current study (see Table 6) indicated that, there was marked statistical difference between mean of total score of opinions and attitudes toward HIV/AIDS and sex at posttest for both Preparatory students and secondary students with females have better attitude than males. This is in contrast with Kumar et al [32] who reported that student boys have significantly healthier attitudes towards HIV patients than student girls.…”
Section: Means Of Total Score Of Opinions and Attitude Toward Patientcontrasting
confidence: 81%
“…As the rate of people infected with HIV/AIDS increases, the need of improving knowledge and attitude among dentists become a necessity [10,11]. In this study, the total mean of knowledge and attitude were observed as 69.65% and 68.54% respectively.…”
Section: Discussionmentioning
confidence: 63%